African traditional religion - Lugira, Aloysius Muzzanganda (New York : Chelsea House Publishers, 2009)
Explores the many manifestations of African religious belief and their expressions, in the past and in the present, as well as the hopes for the future.
Chelsea House and Facts on File are both imprints of Infobase Publishing.
Includes bibliographical references (p. 134-135) and index.